The profile of drug resistance of Mycobacterium tuberculosis and clinical features of extrapulmonary resistant tuberculosis among children living in Lviv region, Ukraine - Z.I. Piskur; L.I. Pylypiv; O.M. Shvets; O.P. Kostyk; M.I. Sakhelashvili (Group of Companies Med Expert, LLC, 2022)
Pediatric tuberculosis (TB) is a serious infectious disease that affects many children worldwide and is more likely to be extrapulmonary than adult TB. The purpose - to analyze the profile of drug resistance of Mycobacterium tuberculosis and clinical features of extrapulmonary resistant (EPR) TB among children from Lviv region, Ukraine. Materials and methods. We analyzed all cases of EPR TB (n=23) and extrapulmonary sensitive (EPS) TB (n=24) among 478 medical charts of children, who were hospitalized in the Lviv Anti-TB hospital during 2013-2020. Results. It was found out that EPR TB was diagnosed significantly more often at the age of 1 year and up to 3 years old than EPS TB and significantly less often - among children aged 4-7 years. The children with EPR TB were significantly more likely to live in rural areas and they were significantly more likely to be from families with less than 2 children, compared to EPS TB. The children with EPR TB were more often diagnosed with meningeal and central nervous system (CNS) TB, less often - with TB of the bones and joints, only they had TB of the intestine, compared to EPS TB. Miliary pulmonary TB and the predominance of bilateral process were more common at EPR TB. Among children with EPR TB, rifampicin-resistant TB was significantly more common found than the risk of multidrug-resistant TB (MDR-TB) and monoresistant TB. The resistance profile of MDR-TB showed that 17.4% are resistant to the combination of HR (H-isoniazid, R-rifampicin), 8.6% - to HRES (E-ethambutol, S-streptomycin), 4.3% - to НRS. Among 43.5% of children with EPR TB the contact with a TB patient was not established. At the same time, only a third of children who had came into contact with bacterial exсretors were under dispensary observation and only about 9% received chemoprophylaxis. Conclusions. In order to prevent the development of EPR TB, it is necessary to improve TB prevention measures among the most vulnerable segments of the population. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institutions. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.